The importance of the coastal geomorphology study in geography lessons through field work - Sacramento, Ana Claudia Ramos; Barroso, Taíza Nunes de Souza (Geosaberes; Vol 10 No 22 (2019): Sept - DecDO - 10.26895/geosaberes.v10i22.811, 2019)
Brazil is characterized as a coastal country, that is, in all its territorial extension there are characteristics of coastal environments that directly or indirectly influence society, so it is important to learn in the classroom. Thus, the purpose of this text is to analyze the importance of the contents of coastal geomorphology by means of field work for one class of High School in 10 th grade. The teaching of geography can permeate the geomorphological characteristics of the Brazilian coast, specifying their differences and particularities, that is, each territory of the country has a characteristic coastal environment, as is the case of the Pedrinhas Beach in São Gonçalo-RJ. The results obtained through the Field Work in the teaching of Coastal Geomorphology were greater approximation of students with the coast of gonçalense, awareness of the uses of Praia, the question of environmental impacts on the beach, observation and importance of the mangrove as coastal vegetation.